Desmoplastic melanoma: an updated immunohistochemical analysis of 40 cases with a proposal for an additional panel of stains for diagnosis. (27th January 2016) - Plaza, Jose A.; Bonneau, Peter; Prieto, Victor; Sangueza, Martin; Mackinnon, Alexander; Suster, David; Bacchi, Carlos; Estrozi, Bruna; Kazakov, Dmitry; Kacerovska, Denisa; Falconieri, Giovanni; Suster, Saul
Abstract : Desmoplastic melanoma (DM) is histologically characterized by a proliferation of spindle melanocytes dispersed in a collagenous stroma that can be mistaken for a variety of neoplasms. The purpose of this study was to analyze 40 cases of DM with a comprehensive panel of immunohistochemical markers (KBA.62, p16, Ezrin, WT‐1, MITF‐1, SOX‐10, CD117, SOX‐2, nestin, PNL2, p75, MART‐1, gp100 and S100p) to obtain a more complete understanding of the potential use of these antibodies in the diagnosis of DM. We found that all cases of DM expressed p16, WT‐1, SOX‐10, nestin and S100p and 95% of cases expressed p75. There was variable expression with Ezrin, SOX‐2, KBA.62, MART‐1 and HMB‐45. Most DMs did not express MITF‐1, PNL2 and CD117. Conditions that may enter in the histologic differential diagnosis of DM, including dermal scars, fibromatosis and dermatofibromas were also studied. Nearly all control cases also stained positive for p16 but were negative for WT1, SOX10, nestin, p75 and S‐100p, as well as for most of the other markers tested. We conclude that a panel of S‐100p, WT1, SOX10, p75 and nestin may constitute the optimal panel with the most sensitive and specific combination of immunostain available for the diagnosis of DM.